The Effectiveness of the Aswaja Character-Based Project-Based Learning Model in Improving the Narrative Writing Ability of Students at Universitas Islam Makassar - Erniati, Erniati; Hafiz Bin Hatta, Muhammad; Salam, Selmiana; Jumiati, Jumiati; Arief, Herawati (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aimed to examine the effectiveness of the Project-Based Learning (PjBL) model integrated with Aswaja character values in improving students’ narrative writing skills. Specifically, it sought to determine whether students taught using the PjBL-Aswaja model show significantly higher writing performance compared to conventional instruction. Method: A quantitative quasi-experimental design with a pretest–posttest control group was employed. The study involved 64 students from two classes of the Indonesian Language Education program, selected through purposive sampling. The experimental group received the PjBL-Aswaja intervention, while the control group received conventional instruction. Narrative writing ability was measured using a performance-based writing test before and after the intervention. Data were analyzed using descriptive statistics, paired sample t-tests, independent sample t-tests, ANCOVA, and effect size calculations (Cohen’s d and partial η²). Results: The findings indicate that both groups improved after instruction; however, the experimental group demonstrated a significantly greater increase in narrative writing performance (gain score = 11.90) compared to the control group (gain score = 5.06), with large effect sizes (Cohen’s d = 1.02; partial η² = 0.30, p < 0.001). ANCOVA results confirmed that the PjBL-Aswaja model significantly enhanced students’ posttest scores even after controlling for pretest performance. Novelty: This study highlights the integration of character values from Aswaja within a project-based learning approach as an effective method to foster both cognitive and moral development in higher education writing courses. The findings provide practical and theoretical implications for character-based instructional design in narrative writing pedagogy.